Prevalence and Antibiotic Susceptibility of Isolated Acinetobacters from Blood Culture in Shariati Hospital - H Yazdanbod; A Rasti; Y Erfani (Tehran University of Medical Sciences, 2010)
Background and Aim: Acinetobacters are opportunistic pathogens and one of the important agents of nosocomial infections that causes many infections like septicemia and pneumonia. For resistance to antibiotics acinetobacters are mentioned as a healthcare system complications and are transmitted by the hands of healthcare workers. This research has performed in order to determine prevalence and antibiotic susceptibility of isolated acinetobacters from blood cultures.Material and methods: This study was performed during a nine months period in shariati hospital. All 750 positive blood cultures were distinguished and prevalence of acinetobacter and antibiotic susceptibility of isolated acinetobacters were determined using disk diffusion agar method. Data were analyzed using SPSS software .Results: According to our findings,133 blood cultures were positive for acinetoloacters(17.7% of cases). The most observed cases were isolated from emergency ward of hospital (65.5%). Antibiogram results using ciprofloxacin ,cotrimoxasol,gentamicin, ceftazidime, amikacine, tobramicine and ceftriaxone, showed maximum sensitivity to ciprofloxacine(91%) and cotrimoxazole (57.5%) and maximum resistance to ceftriaxone respectively.Discussion and Conclusion: Because the most acinetobacter isolation was from emergency ward of hospital, it seems that a part of such infections is more due to contamination than real infection. Therefore it is recommended that a prospective cohort study considering standard and sterile conditions during sampling , by considering patients clinical features has to be performed.